The End of Desire: On the Meaning of תשׁוקה in the Hebrew Scriptures and the Dead Sea Scrolls - Condren, Janson C. (The journal of Hebrew scriptures, 2024)
Despite the long-standing tradition of translating תשׁוקה as "desire" in its three biblical occurrences (Gen 3:16; 4:7; Cant 7:11 [Eng. 10]), recent studies have put forth alternatives such as "turning, return," "preoccupation, devotion" and "driving." This essay examines these possibilities in light of the usage of תשׁוקה in the Dead Sea Scrolls (1QM 13:12; 15:10; 17:4; 1QS 11:22; 4QInstrb 2:4). The meaning "desire" is shown to be particularly problematic, not only as a result of its absence in the earliest biblical versions, but also due to the expression לעפר תשׁוקתו immediately after a depiction of mankind being created from dust (עפר) in 1QS 11. The standard translation, "for dust is [mankind’s] desire," appears incongruous, and parallels in Hodayot reinforce the likelihood that a "return" to dust is in view. The meanings "preoccupation, devotion" and "driving" also lack plausibility in 1QS 11, and "turning, return" proves problematic in 1QM 13 and 15. It is suggested the semantic range of תשׁוקה includes both "a focused movement toward" and "a focused movement back toward." As such, it denotes "preoccupation, devotion" in most of its occurrences, yet indicates "return" in 1QS 11, and possibly Gen 3:16.